ATHLETE TRACK AND FIELD RECRUITMENT IN SPORT STUDENT TRAINING CENTER - Lesia Nini; Y Touvan Juni Samodra; Edi Purnomo Purnomo (Universitas Sriwijaya, 2020)
Athlete recruitment was importance in sport achievement. If have good athlete based on good talend selected, so it will be greatest opportunities height performance achievement. PPLP given facilities and opportunities for student athlete from secondary and senior high school. The purpose of this study is to determine the management of athlete recruitment, athlete training and training programs and supporting infrastructure for athlete training. The research method used in this is qualitative. Sources of data in this study were athletes, coaches, PPLP managers and administrators of PASI KALBAR. The instruments in this study were observation, semi-structured interviews, field notes and documentation. The technique of checking the validity of the data is by triangulation. The recruitment athlete had charged in 2017, that was recruitment depend on coach recommendation. Coaches made recommendation based on athlete achievement. In 2017 that recruitment based on KEMANPORA rules. From 2012 to 2019 not yet showed significance achievement performance. Base on the data research showed, with new selection recruitment did not effect on achievement.